2021
DOI: 10.17051/ilkonline.2021.01.91
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Spatial Ability and Geometric Thinking Level of Prospective Elementary School Teachers Using the Rasch Model

Abstract: The objectives: (1) measuring spatial ability and geometric thinking level of Prospective Elementary School Teachers (PGSD students), (2) analyzing difficulties faced on a certain spatial ability. The study used a mixed-method quantitative and qualitative. Researchers developed test items to measure the spatial ability and geometric thinking of 139 Prospective Elementary School Teachers (PGSD students), Universitas Negeri Semarang. The sampling method employed was cluster random sampling, while three students … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Van Hiele (Van de Walle, 2018) Research on geometry skills of students of Pendidikan Guru Sekolah Dasar (PGSD)/Elementary School Teacher Education Degree Program, Faculty of Education, Universitas Negeri Semarang, showed that the students' characteristics on the types of spatial ability and geometric thinking level are essential to induce the geometry lecture strategy. The results of the research data analysis indicated that the students were still in the sufficient category for the two abilities that had an effect on learning geometry (Trimurtini et al, 2021). When presented with application questions involving multiple geometric concepts, students continue to struggle.…”
Section: Figure 1 Proportion Of Five Scopes Of Mathematics Materials ...mentioning
confidence: 94%
“…Van Hiele (Van de Walle, 2018) Research on geometry skills of students of Pendidikan Guru Sekolah Dasar (PGSD)/Elementary School Teacher Education Degree Program, Faculty of Education, Universitas Negeri Semarang, showed that the students' characteristics on the types of spatial ability and geometric thinking level are essential to induce the geometry lecture strategy. The results of the research data analysis indicated that the students were still in the sufficient category for the two abilities that had an effect on learning geometry (Trimurtini et al, 2021). When presented with application questions involving multiple geometric concepts, students continue to struggle.…”
Section: Figure 1 Proportion Of Five Scopes Of Mathematics Materials ...mentioning
confidence: 94%
“…While it is possible to enhance spatial visualization ability through appropriate teaching techniques, many students struggle with low spatial visualization skills (Lin et al, 2015;Miller & Halpern, 2013;Newcombe, 2010;Sorby, 1999). Despite opportunities available for both teachers and students to learn spatial visualization skills, many teachers still lack the necessary experience in effectively teaching them (Miller & Halpern, 2012;Trimurtini et al, 2021).…”
Section: Introductionmentioning
confidence: 99%